“Watershed moment” or “more money to steal”? Justice framings of South Africa’s COP26 just energy transition deal in news media vs. Facebook comments - Okoliko, Dominic Ayegba; Iqani, Mehita (Frontiers in Communication, 2025)
This study examines what “just” visions underpin how South Africa’s COP26 energy transition deal was framed in news media and Facebook public discourse. At the 2021 Glasgow summit, South Africa secured an 8.5 billion Just Energy Transition Partnership (JETP) deal to support the decarbonization of its coal-dependent energy system, sparking intense national debate. Energy communication research offers a valuable lens for understanding how such deliberations unfold, highlighting public perceptions and attitudes toward a just energy transition. Yet, attention to justice dimensions in public conversations on energy transitions—particularly in Africa—remains limited, and cross-platform discourse comparisons are rare. Addressing these gaps, we analyzed 53 news publications from 17 South African mainstream media outlets and 743 Facebook comments on posts about the JETP using qualitative frame and network analysis, focusing on justice framing, actor visibility, and temporal orientation. Findings reveal stark asymmetries. Procedural justice appeared prominently in both spaces (58%) but served divergent purposes: media framed it to legitimize state-led pacing, while Facebook emphasized governance failures and systemic distrust. Media narratives privileged elite voices—government, experts, business—with workers and communities receiving only 1% visibility. In contrast, Facebook reflected grassroots perspectives grounded in lived experience and socio-economic precarity. Media discourse was future-focused and optimistic; Facebook was rooted in historical grievances and skepticism. The study discusses implications for South Africa’s energy transition, highlighting discursive power imbalances and their significance for just-transition governance and communication.